Human area V5 and motion in the ipsilateral visual field - Ffytche, D. H.; Howseman, A.; Edwards, R.; Sandeman, D. R.; Zeki, S. (The European journal of neuroscience, 2000)
We have studied area V5 of the human brain with visually‐evoked potential (VEP) and functional magnetic resonance imaging (fMRI) methods, using hemifield motion stimuli. Our results confirmed the presence of an ipsilateral field representation in V5 and found: (i) a delay in the ipsilateral response in V5, irrespective of the hemifield stimulated; (ii) a longer ipsilateral delay for left hemifield than for right hemifield stimulation; and (iii) in a patient with a section of the splenium, an absent ipsilateral response for right but not left hemifield stimulation. Together with neurophysiological and anatomical evidence in the monkey, our non‐invasive spatial and temporal imaging studies in man reveal that ipsilateral V5 is activated by motion signals transferred from contralateral V5. The asymmetry of ipsilateral delay in normal subjects and the asymmetrical loss of ipsilateral response following splenial section imply that signals related to visual motion are transferred from one V5 to the other through two segregated pathways.